THE INFLUENCE OF MOTIVATION, FINANCIAL LITERACY, AND SOCIAL MEDIA FINANCIAL PLATFORMS ON STUDENT INVESTMENT INTEREST - Ozdemir, Metin; Sari, Avid Leonardo; Irwandi, Irwandi (KOMITMEN: Jurnal Ilmiah Manajemen, 2021)
The purpose of this study was to determine whether there was an influence of motivation, financial literacy, and social media financial platforms on student investment interest. This research uses quantitative research with a descriptive analysis approach. The types of data used in this study are primary data and secondary data. The population of this study was all students majoring in management at the University in Bandung. At the same time, the sample in this study consisted of 50 students using purposive sampling—data collection techniques using the questionnaire method. The type of questionnaire used is a closed and structured questionnaire. The questions or statements do not give freedom to the respondents to provide answers and opinions according to their wishes because the responses have been provided—analysis of research data using Descriptive Analysis, Validity Test, Reliability Test, and Partial Hypothesis Testing. Based on the research and data analysis results, it can be concluded that Extrinsic Motivation, Financial Literacy, and Financial Platforms on social media have a positive and significant effect on the investment interest of students majoring in university management in the city of Bandung.